1960 AHSME Problems/Problem 22

Revision as of 20:15, 10 May 2018 by Rockmanex3 (talk | contribs) (See Also)

Problem 22

The equality $(x+m)^2-(x+n)^2=(m-n)^2$, where $m$ and $n$ are unequal non-zero constants, is satisfied by $x=am+bn$, where:

$\textbf{(A)}\ a = 0, b \text{ } \text{has a unique non-zero value}\qquad \\ \textbf{(B)}\ a = 0, b \text{ } \text{has two non-zero values}\qquad \\ \textbf{(C)}\ b = 0, a \text{ } \text{has a unique non-zero value}\qquad \\ \textbf{(D)}\ b = 0, a \text{ } \text{has two non-zero values}\qquad \\ \textbf{(E)}\ a \text{ } \text{and} \text{ } b \text{ } \text{each have a unique non-zero value}$

Solution

Expand binomials, combine like terms, and subtract terms from both sides. \[x^2 + 2xm + m^2 - x^2 - 2xn - n^2 = m^2 - 2mn + n^2\] \[2xm + m^2 - 2xn - n^2 = m^2 - 2mn + n^2\] \[2xm - 2xn - n^2 = -2mn + n^2\] Get all the x-terms on one side and factor to solve for x. \[2xm - 2xn = -2mn + 2n^2\] \[2x(m-n) = -2n(m-n)\] Since $m \not= n$, both sides can be divided by $m-n$. \[x = -n\] That means $a = 0$ and $b = -1$, so the answer is $\boxed{\textbf{(A)}}$.

See Also

1960 AHSC (ProblemsAnswer KeyResources)
Preceded by
Problem 21
Followed by
Problem 23
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40
All AHSME Problems and Solutions
Invalid username
Login to AoPS